Pengaruh Audit Tenure, Ukuran KAP, Ukuran Perusahaan Klien Terhadap Kualitas Audit Perusahaan di Bursa Efek Indonesia - Fitri Andriani; Rindi Meilani; Chandra Evendi Pardede; Wenny Anggeresia Ginting (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This quantitative research aimed to explain and describe the impacts of audit tenure, KAP size and company size in industrial market in Indonesia in 2016-2018. The population included 154 companies, from which samples were randomly selected based on these following criteria is Industrial market of Indonesia 2016-2018, Incomplete financial statement 2016-2018, Unregistered names in industrial market 2016-2018. Companies conducted independent audit without explanation 2016-2018, and Financial statements were published between 2016-2018. There were 105 companies sampled in this research with 315 financial statements for 3 year-period. The data were analyzed descriptively and using logistic regression test. The results of the logistic analysis showed that Audit Tenure, KAP Size, and Company Size had a positive influence on the dependent variable of this research. Keywords : Audit Tenure, KAP Size, Company Size, Audit Quality, Manufacturing Company, Indonesia Stock Exchange